Who has the right to the city? Reform Jewish rituals of gender-religious resistance in Tel Aviv-Jaffa. Issue 9 (2nd September 2022) - Ben-Lulu, Elazar
Abstract: Reform Judaism is one of the dominant religious movements in the contemporary Jewish world and is known primarily for its liberal approach, such as advocating for gender equality in Jewish religious practices. In Israel, however, the Reform community has been excluded by the hegemonic Jewish Orthodox community and is seen as an outsider that threatens the very continuation of the Jewish people. This article examines Reform rituals that are conducted in the urban space of the Tel Aviv-Jaffa area and posits that the execution of the rituals outside the congregation's permanent houses of prayer manifests gender-religious resistance against the Jewish Orthodox hegemony, as well as against patriarchal traditions and heterosexual constructions. It is further claimed that the Reform community has positioned itself as an alternative, more egalitarian religious agent in the Israeli public space, which positively impacts the goal of the feminist and the LGBTQ+ movements to gain gender recognition.